Traveling Salesman, Greedy Coin and Other Optimization Problems in Python in One Hour - Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Learn the foundations of optimization Python for Business Analytics Topics include: * TSP or Traveling Salesman Problem * How to create Python Greedy Algorithms * The foundations of Deep Learning Algorithms * Using Github Codespaces to edit Python * Solving the Greedy Coin problem in Python * How to use AWS Data Brew to do Business Analytics in the Cloud * How to use AWS Quicksite to do Business Analytics * How to use AWS AutoML tools for Business Analytics.